Annual report - Cocoa Research Institute (Ghana) (Tafo : The Institute, 1987)
Report of the Cocoa Research Institute for the period 1982/83-1984/85.The report consist of various activities of the cocoa plantation by the research institute of Ghana.
rpm 31/01/2019
Loans
Keywords: Cocoa; Cocoa Research Institute Institute; Ghana